Environmental and economic benefits of saline-sodic soil reclamation using low-quality water and soil amendments in conjunction with a rice-wheat cropping system - Murtaza, G.; Ghafoor, A.; Owens, G.; Qadir, Manzoor; Kahlon, U.Z. (Wiley, 2009)
A combination of appropriate crop rotation(s) and management interventions has the potential to transform saline-sodic soil and water resources from an environmental burden into an economic asset. We carried out 2-year field studies in the Indus Basin of Pakistan to evaluate different irrigation and soil management options of using saline-sodic waters (SSW) and soils for reclamation and for growing salt-tolerant cultivars of rice (SSRI-8) and wheat (SIS-32). These soils have variable levels of salinity and sodicity (ECe 9-44 dS m)1 and SAR 83-319). The treatments on both the sites were the same and consisted of: (1) Irrigation with SSW, (2) Irrigation with freshwater (FW), (3) Soil application of gypsum at 100 % gypsum requirement of soil + SSW (G + SSW), (4) G + one irrigation with SSW and one with FW (G + 1SSW + 1FW), (5) G + two irrigations with SSW and one with FW (G + 2SSW + 1FW), (6) Farm manure at 25 Mg ha)1 each year before rice + one irrigation with SSW and one with (FW FM + 1SSW + 1FW) and (7) FM + two irrigations with SSW and one with FW (FM + 2SSW + 1FW). Rice was grown as the first crop. After harvesting final wheat crop (fourth in sequence), maximum decrease in bulk density and increase in infiltration rate was observed with G + 1SSW + 1FW while FM + 1SSW + 1FW treatment showed higher decrease in pHs and ECe. Significantly the highest decrease in SAR occurred at both sites with G + 1SSW + 1FW. Maximum yields of rice and wheat were generally observed with G + 1SSW + 1FW. The crop yield and economic benefits with treatments showed a positive correlation with that of improvement in soil physical and chemical properties. Overall, the greatest net benefit was obtained from G + 1SSW + 1FW treatment. We also found that the farmers' management skills were crucial in the overall success in improving crop yields during reclamation of saline-sodic soils. Based on the results of this study, we propose that SSW could be used to reclaim saline-sodic soils by using a rice-wheat rotation and a site-specific combination of soil amendments and water application strategies.